Patients experience of trauma adapted yoga as a health promoting activity in forensic psychiatric care - Sofie Lundström; Nóra Kerekes; Catrin Johansson (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Although the effects of yoga on psychiatric symptoms in psychiatric care are gaining increasing recognition, research within forensic psychiatric care, particularly on subjective experiences, remains limited. To address this gap, the present study aims to describe patients’ experience of trauma-adapted yoga (TAY) as a health-promoting activity in forensic psychiatric care. Methods Twelve individual semi-structured interviews with patients in forensic psychiatric care were conducted, and data were analysed using inductive content analysis. Findings The patients’ experience of TAY as a health-promoting activity was captured in an overarching theme, “To feel that one is connected to mind, body, and soul in a way that can promote a sense of well-being in an uncertain existence”. This overarching theme contained four themes: Strengthening the body, finding a calm place within oneself, something to do solely for oneself but together with others, and prerequisites for doing yoga. Conclusion The findings emphasize that TAY has the potential to be a valuable health-promoting activity for patients in forensic psychiatric care by facilitating their resources to manage stressors in everyday life. Therefore, it should be offered as a complement to other treatments to promote patients’ health and well-being in forensic psychiatric care.